Why some Pharmacists Make the Leap and Others do not “From Good to Great Pharmacists” - Elshenawy, Rasha Abdelsalam; Mahmoud, Fatma-elzahraa Ahmed (Journal of Pharmacy Practice and Community Medicine)
Purpose: The purpose of this study is to define the requirements needed to be an Ideal pharmacist, in addition to determining the best traits that characterize the ideal pharmacist, which can help in explaining the quality indicators for leadership practicing. Methods: This is a descriptive study that was carried out through an online Google Drive survey, in the form of a questionnaire, to assess the skills needed by pharmacists. The data collection tool website was available mid- December 2019 through first February 2020. Descriptive statistics were used to report results. Results: Survey respondents were 905 pharmacists from different countries such as Egypt (384), UAE (75), KSA (326), etc. from different specialties. The most important traits of the great pharmacist as reported by the respondents was the ability of an ideal pharmacist to manage and discuss mistakes and to solve any medical problems. The most important reported skills included the skills of analytical, computer, communication, leadership, management, mentorship, medical research, and clinical practice. Another finding from the survey is related to the preferred expertise to be specialized. Moreover, continuing medical education (CME) programs can play an essential role in enhancing therapeutic and leadership skills. Conclusion: The terms and definitions for great leader may change with the times; however, it is important to understand the skills and abilities needed to lead. The ability to lead effectively is based on several skills, including communication, managing, and solving mistakes, clinical practicing, and integrity.
Keywords: Effectiveness; Continuous Education; Leadership; Management Skills; Pharmacy